Investigation of Electrical Characteristics on 25-nm InGaAs Channel FinFET Using InAlAs Back Barrier and Al2O3 Gate Dielectric. (23rd February 2017) - Lin, M. H.; Lin, Y. C.; Lin, Y. S.; Sun, W. J.; Chen, S. H.; Chiu, Y. C.; Cheng, C. H.; Chang, C. Y.
Abstract : We investigated an N-type III–V FinFET with a 25-nm In0.53 Ga0.47 As channel and a 300-nm In0.52 Al0.48 As barrier layer on an InP substrate. The In0.52 Al0.48 As barrier layer is used to suppress leakage current from the InP substrate and the 10-nm Al2 O3 film deposited by atomic layer deposition (ALD) can be a robust gate dielectric to mitigate interface traps. The on to off current ratio is approximately three orders of magnitude, the subthreshold swing (SS) is 350 mV/dec, and the maximum driving current density is 130 μA/μm at VG = 1.5 V for InGaAs FinFET with a fin width of 40 nm and gate length of 200 nm.